Unravelling Secondary Brain Injury: Insights from a Human-Sized Porcine Model of Acute Subdural Haematoma - Thomas Kapapa; Vanida Wernheimer; Andrea Hoffmann; Tamara Merz; Fabia Zink; Eva-Maria Wolfschmitt; Oscar McCook; Josef Vogt; Martin Wepler; David Alexander Christian Messerer; Claire Hartmann; Angelika Scheuerle; et al. (Cells)
Traumatic brain injury (TBI) remains one of the leading causes of death. Because of the individual nature of the trauma (brain, circumstances and forces), humans experience individual TBIs. This makes it difficult to generalise therapies. Clinical management issues such as whether intracranial pressure (ICP), cerebral perfusion pressure (CPP) or decompressive craniectomy improve patient outcome remain partly unanswered. Experimental drug approaches for the treatment of secondary brain injury (SBI) have not found clinical application. The complex, cellular and molecular pathways of SBI remain incompletely understood, and there are insufficient experimental (animal) models that reflect the pathophysiology of human TBI to develop translational therapeutic approaches. Therefore, we investigated different injury patterns after acute subdural hematoma (ASDH) as TBI in a post-hoc approach to assess the impact on SBI in a long-term, human-sized porcine TBI animal model. Post-mortem brain tissue analysis, after ASDH, bilateral ICP, CPP, cerebral oxygenation and temperature monitoring, and biomarker analysis were performed. Extracerebral, intraparenchymal–extraventricular and intraventricular blood, combined with brainstem and basal ganglia injury, influenced the experiment and its outcome. Basal ganglia injury affects the duration of the experiment. Recognition of these different injury patterns is important for translational interpretation of results in this animal model of SBI after TBI.